PEMODELAN DAN SIMULASI PROSES SURPLUS PADA BISNIS ASURANSI - Hutomo Atman Maulana; Erma Domos (Politeknik Negeri Bengkalis, 2018)
Basic insurance business is public trust. Insurance companies must pay attention to the systems and procedures for the payment of claims problem which is not simple. One of the important thing is when determining premium, because if it is too high could lead the company out of competition with the competitor. In the other hand, it is too low could lead the company lack of cash to handle claim which bring a negative impact for the company. This research aimed to give illustration of surplus in insurance business in a year period through determination of premium income and stochastic modelling in number and amount of claims. This model could be used by insurance company to take decision when determining premium whether surplus or ruin. The research used Exponential and Gamma distribution to model time of arrival and amount of claim respectively. The result show that the minimum premium could be found to get minimum surplus and avoid ruin.